The Development of a Kinetic Model for Biochar Gasification with CO2: Comparison Between a Thermogravimetric Analyzer and a Fluidized Bed Reactor - Luis Reyes; Michael Jabbour; Lokmane Abdelouahed; Bechara Taouk (Fuels)
This study presents the development of a kinetic model for the gasification of biochar with carbon dioxide and compares the results obtained using a thermogravimetric analyzer (TGA) and a fluidized bed reactor (FBR). The kinetic experiments investigated the effects of the CO2 partial pressure (0.33–1 atm), temperature (800–1000 °C), and CO2/C ratio (3.5–10.5). Three structural models, the shrinking core model (SCM), volumetric model (VM), and power-law model (PLM), were evaluated for their ability to predict experimental results. The results demonstrated that increasing the temperature, CO2 partial pressure, and CO2/C ratio enhanced the gasification rate, reducing the time required for complete biochar conversion. The apparent activation energy for both reactors was similar (156–159 MJ/kmol), with reaction orders of 0.4–0.49. However, the kinetic models varied significantly between setups. In the TGA, the PLM provided the best fit to experimental data, with standard deviations of 2.6–9%, while in the FBR, the SCM was most accurate, yielding an average deviation of 1.5%. The SCM effectively described the layer-by-layer char consumption, where gasification slowed at high conversion levels. Conversely, the PLM for the TGA revealed a unique mathematical function not aligned with traditional models, indicating localized reaction behaviors. This study highlights the inability to directly extrapolate TGA-derived kinetic models to FBR systems, underscoring the distinct mechanisms governing char consumption in each reactor type. These findings provide critical insights for optimizing biochar gasification across diverse reactor configurations.